2004
DOI: 10.1161/01.str.0000133130.20322.9f
|View full text |Cite
|
Sign up to set email alerts
|

Very Long-Term Outcome After Stroke in Auckland, New Zealand

Abstract: Background and Purpose-Limited information exists on the long-term outcome from stroke. We aimed to determine survival and health status at 21-year follow-up of patients who participated in a population-based stroke incidence study undertaken in Auckland, New Zealand. Methods-During 12 months beginning March 1, 1981, half of all residents of Auckland with acute first-ever or recurrent stroke (nϭ680) were assessed and followed up prospectively during the next 2 decades. In 2002, their vital status and health-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 37 publications
2
46
0
2
Order By: Relevance
“…Survival after first or recurrent stroke has been reported to be <10% after 20 years, the risk factors for death were age, previous stroke, subtype of stroke, and different stroke features (Anderson et al., 2004). Lower mortality rates for patients with TIA versus stroke after one year were reported by a study in Japan after hospital discharge (7% for stroke patients and 3.5% for TIA patients) (Kimura et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Survival after first or recurrent stroke has been reported to be <10% after 20 years, the risk factors for death were age, previous stroke, subtype of stroke, and different stroke features (Anderson et al., 2004). Lower mortality rates for patients with TIA versus stroke after one year were reported by a study in Japan after hospital discharge (7% for stroke patients and 3.5% for TIA patients) (Kimura et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 145 individuals, 73% were independent in activities of daily living (Barthel index score 95-100), 13% had minor dependence (score 60-90), and 14% had major dependence (score 0-55). The assessment of functional status showed that 71% scored ≤2 on mRS, that is, they had no or only slight disability, whereas 14% had moderate disability (mRS score 3) and 15% were more severely disabled (mRS score [4][5]. No significant sex differences in functional status were observed.…”
Section: Objective Life Situation and Functional Statusmentioning
confidence: 93%
“…Currently, data largely come from short-term cohort studies with limited follow-up (usually up to 1 year) and subject to selection bias because they are not population-based. In population-based studies, quality of life has been assessed between 2 and 21 years after stroke, [7][8][9][10][11][12] activities of daily living up to 21 years in Auckland, 7 up to 5 years in Perth, Australia, 13 and 5 years in south London. 14 Clinically defined outcomes may be of limited use in assessing long-term need after stroke and developing services to meet needs.…”
mentioning
confidence: 99%